A wet-chemical route for macroporous inverse opal Ge anodes for lithium ion batteries with high capacity retention. Issue 1 (8th November 2017) - Geier, Sebastian; Jung, Roland; Peters, Kristina; Gasteiger, Hubert A.; Fattakhova-Rohlfing, Dina; Fässler, Thomas F.
Abstract : Germanium holds great potential as an anode material for lithium ion batteries due to its high specific capacity and its favorable properties such as good lithium ion diffusivity and electronic conductivity. Abstract : Germanium holds great potential as an anode material for lithium ion batteries due to its high specific capacity and its favorable properties such as good lithium ion diffusivity and electronic conductivity. However, the high cost of germanium and large volume changes during cycling, which lead to a rapid capacity fading for bulk Ge materials, demand for nanostructured thin film devices. Herein we report the preparation and electrochemical properties of thin films of porous, inverse opal structured Ge anodes obtained via a simple, up-scalable wet-chemical route utilizing [Ge9 ] 4− Zintl ions. In the absence of conductive additives, they show high initial capacities of >1300 mA h g −1 and promisingly high coulombic efficiencies of up to 99.3% and deliver over 73% of their initial capacity after 100 cycles when cycled vs. metallic lithium. In contrast to many other porous structured Ge electrodes, they show very little to almost no capacity fading after an initial drop, which makes them promising candidates for long life applications.